2012
DOI: 10.15407/fz58.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c as an amplifier of ROS release in mitochondria

Abstract: Cytochrome c as an amplifier of ROS release in mitochondria The influence of exogenous cytochrome c on reactive oxygen species (ROS) formation and its dependence on mitochondrial permeability transition pore (MPTP) opening is studied in rat liver mitochondria. Fluorescent probe dichlorofluorescein (DCF) was used. It was shown that MPTP activation by increasing concentrations of Ca 2+ in the medium results in the increase in mitochondrial ROS production and oxygen consumption, but the decrease in matrix calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Mitochondria play a crucial part in the cell growth and death and possess the function of ROS generation and detoxification ( 40 , 41 ). It has been demonstrated that at high concentration, ROS might lead to severe injury to cells, which referred to the ‘oxidative stress’ ( 42 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria play a crucial part in the cell growth and death and possess the function of ROS generation and detoxification ( 40 , 41 ). It has been demonstrated that at high concentration, ROS might lead to severe injury to cells, which referred to the ‘oxidative stress’ ( 42 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cytochrome C can transfer electron directly to p66 Shc , a redox enzyme, to generate ROS [47]. The heme center of cytochrome C may also act to enhance ROS production [48].…”
Section: Discussionmentioning
confidence: 99%
“…As we have shown earlier, in low-conductance states mPTP releases Ca 2+ in exchange for protons [18], takes part in Ca 2+ cycling and oxygen consumption without much affecting ΔΨ m in rat liver mitochondria [19]. Based on our previous studies, reversible mPTP opening in low conductance states in liver mitochondria contributed to ROS production and caused mild uncoupling of Oxphos [19,20].…”
mentioning
confidence: 58%